ANALISIS NORMATIF TINDAK PIDANA PERZINAHAN DILIHAT DALAM PERSPEKTIF HUKUM ISLAM - Iman Hidayat (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
One of the crucial problems in the renewal  of KUHP is the formulation of adultery criminal act. Especially when referred to legal life historical experience in Indonesia, there are various legal systems thot exist at the same time. It means that the renewal of adultery criminal act must consider the possibility of legal system out of one system to be included in the new formulation of KUHP. It is intresting to analyze if this problem is faced with the possibility of Islamic law contribution which is directing into two things, I.e obtaining  a clear picture of the adultery criminal act according to the Islamic law compered with KUHP and RKUHP, and the relevance of criminal act in Islamic law to be the source of he farmulation of the new national KUHP. Keyword : KUHP, Adultery, Islamic Law